Entrepreneurial mindset: a systematic literature review and empirical study of MSMEs in the special region of Yogyakarta - Utami Tunjung Sari; Bhenu Artha; Bahri; Niken Permata Sari; Asha Mussa Mallya; Cynta Alya Dinka (Universitas Widya Mataram, 2026)
The intersection of entrepreneurial mindset, artificial intelligence (AI), and business performance represents a dynamic research area, yet systematic syntheses of these relationships remain limited. This research aims to synthesize empirical evidence examining the connections between mindset development and AI adoption, while empirically evaluating their impact on MSME performance in Yogyakarta. Adopting PRISMA guidelines, a systematic literature review (SLR) analyzed 15 peer-reviewed articles published between 2019 and 2024. This was complemented by an empirical study of 51 MSME owners utilizing multiple linear regression analysis. SLR results indicate that AI integration catalyzes mindset development through cognitive enhancement and experiential learning. Empirical findings confirm that both entrepreneurial mindset and AI use are statistically significant predictors of business performance, collectively explaining 12.6% of the variance. Notably, entrepreneurial mindset exerts a stronger influence than AI adoption. These results imply that digital transformation is most beneficial when grounded in an entrepreneurial approach. Recommendations include integrating generative AI into curricula and fostering strategic AI literacy among practitioners to enhance business sustainability.